Peculiarities of substrate selection for in vivo adaptation of plants-regenerates of rose essential oil - Олійник, О. О. (Scientific Progress & Innovations, 2018)
In research we studied substrates selection for successful adaptation of rose essential oil (variety Lan’) after microclonal propagation. The results showed that the most advisable is to use a mixture of peat and perlite in a ratio of 2:1. The survival rate of plants on the peat mixture with river sand was 70 % after 14 days of adaptation period. In the corresponding period this index was 62 % on a coconut substrate without impurities and 60 % on a coconut substrate with perlite. Using of a single-component substrate for the adaptation of rose essential oil are inadvisable, because the adaptation efficiency doesn’t exceed 50 %.